Changes in polyphenolics during maturation of Java plum (Syzygium cumini Lam.). (October 2017) - Lestario, Lydia Ninan; Howard, Luke R.; Brownmiller, Cindi; Stebbins, Nathan B.; Liyanage, Rohana; Lay, Jackson O.
Abstract: Java plum ( Syzygium cumini Lam.) is a rich source of polyphenolics with many purported health benefits, but the effect of maturation on polyphenolic content is unknown. Freeze-dried samples of Java plum from seven different maturity stages were analyzed for anthocyanin, flavonol, flavanonol and hydrolysable tannin composition by HPLC. Anthocyanins were first detected at the green-pink stage of maturity and increased throughout maturation with the largest increase occurring from the dark purple to black stages of maturation. Levels of gallotannins, ellagitannins, flavonols, gallic acid and ellagic acid were highest at early stages of maturation and decreased as the fruit ripened. For production of antioxidant-rich nutraceutical ingredients, fruit should be harvested immature to obtain extracts rich in hydrolysable tannins and flavonols. The exceptional anthocyanin content of black fruit may prove useful as a source of a natural colorant. Graphical abstract: Highlights: Anthocyanins increase throughout maturation. Gallotannins, ellagitannins and flavonols decrease throughout maturation. Anthocyanin-rich extracts from black fruit show promise as a natural colorant.